2013
DOI: 10.4172/2165-7939.s2-007
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Osteophyte Evolution and its Impact in Cervical Spondylosis: A Literature Review

Abstract: Introduction: In cervical disc disease, the exact location of the posterior osteophyte with relationship to the bodies of the adjacent cervical vertebra at each disc space level, as observed during surgery under operating microscope and correlating it with the histopathological development of the posterior osteophyte has not been documented in literature. A detailed review of literature on the development of posterior osteophytes and its impact on cervical spinal cord is also being reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…15 Disc-osteophyte complexes may directly cause cord compression, or may function as a tether about which the cord stretches and places tension on dentate ligament attachments; both processes likely contribute to symptoms of CSM. 16,17 While multiple studies have showed comparable clinical outcomes following laminoplasty or LF for the surgical treatment of CSM, preoperative sagittal alignment of the cervical spine is often used to guide the treatment choice with significant kyphosis and instability often used as a contraindication to laminoplasty while fixed severe kyphosis is used as a contraindication for LF.…”
Section: Discussionmentioning
confidence: 99%
“…15 Disc-osteophyte complexes may directly cause cord compression, or may function as a tether about which the cord stretches and places tension on dentate ligament attachments; both processes likely contribute to symptoms of CSM. 16,17 While multiple studies have showed comparable clinical outcomes following laminoplasty or LF for the surgical treatment of CSM, preoperative sagittal alignment of the cervical spine is often used to guide the treatment choice with significant kyphosis and instability often used as a contraindication to laminoplasty while fixed severe kyphosis is used as a contraindication for LF.…”
Section: Discussionmentioning
confidence: 99%